The need for practice enhancements and parental empowerment during their child’s day surgery process: A pilot study (Journal of Paediatric Surgeons of Bangladesh, 2024)
Background: Perioperative experiences leave a lasting psychosocial impact on the parents of children undergoing surgery. Methods: A phenomenological study design recruited parents of children undergoing day surgery using purposive sampling. Semi-structured face to face interviews were conducted two weeks postoperatively. Results: Thematic analysis revealed 6 main themes with 12 sub-themes. Although the parents acknowledged the emotional support and tangible assistance from the healthcare team, mostly the themes revealed negative perceptions of the unique processes within paediatric day surgery. Conclusions: Parents’ feelings of anxiety, stress, helplessness and the pressure to be seen as a resource of physical and emotional support during their child’s perioperative period were expressed by them as their needs for additional information and counselling, remote access to the primary healthcare team postoperatively and advice on coping strategies. Practice enhancements using technology and innovative playtherapy in combination with active parental participation may make day surgery a positive experience for both parents and children.Journal of Paediatric Surgeons of Bangladesh (2019) Vol. 10 (1 & 2): 5-14